miR-221, miR-650 and miR-4534 as diagnostic markers in prostate cancer and their relationship with lymphatic invasion - Hekımler Öztürk, Kuyaş; Mutlu İçduygu, Fadime; Özgöz, Asuman; Özorak, Alper (Walter de Gruyter GmbH, 2022)
Abstract Objectives This study aimed to examine the role of miR-221, miR-650, and miR-4534 expressions in the development, pathogenesis, and early diagnosis of prostate cancer. Methods The study included 83 participants: 37 patients with PCa, 31 patients with BPH, and 15 healthy subjects. MiRNA expressions in plasma samples was evaluated by quantitative RT-PCR. Results Plasma miR-221 and miR-4534 levels were significantly upregulated in the PCa and BPH groups compared to the control group. A significant difference was determined between the presence of lymph node metastasis and the expressions of miRNAs. In the ROC analysis of the miRNAs, it was determined that the AUC for miR-221 was 0.737 with a sensitivity of 57% and specificity of 100%, AUC for miR-650 was 0.706 with a sensitivity of 62% and specificity of 93% and AUC for miR-4534 was 0.800 with a sensitivity of 73% and specificity of 93%. Conclusions Overexpression of miR-221, miR-650, and miR-4534 may distinguish PCa and BPH from healthy controls, but seems to be insufficient in differentiating PCa from BPH when used alone or in combination. However, these oncogenic miRNAs may have a role in determining the development and progression of the disease by suppressing the tumor suppressor genes they target.
Keywords: benign prostatic hyperplasia; lymphatic invasion; microrna; biomarker; QD415-436; prostate cancer; Biochemistry; 3. Good health